2014
DOI: 10.1152/ajpregu.00186.2013
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and localization of two types of AQP5 inXenopus tropicalisunder hydration and dehydration

Abstract: expression and localization of two types of AQP5 in Xenopus tropicalis under hydration and dehydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…However, the magnitude and direction of the effect of HgCl 2 on water influx rates suggest that AQPs may play a mainly stabilizing role in water transport in "at-rest" skin. Similar conclusions were made by Ogushi et al (49), who found that HgCl 2 -sensitive AQPs were not constitutively expressed in any great number in at-rest skin, and Shibata et al (64), who found that AQPs were upregulated only in dehydrated animals. Indeed, the antidiuretic hormone arginine vasotocin appears to be required to simulate some AQP-mediated water transport in in vitro skin preps (48).…”
Section: Bd Infection Impairs Cutaneous Water Uptake Rates But Not Tosupporting
confidence: 81%
See 3 more Smart Citations
“…However, the magnitude and direction of the effect of HgCl 2 on water influx rates suggest that AQPs may play a mainly stabilizing role in water transport in "at-rest" skin. Similar conclusions were made by Ogushi et al (49), who found that HgCl 2 -sensitive AQPs were not constitutively expressed in any great number in at-rest skin, and Shibata et al (64), who found that AQPs were upregulated only in dehydrated animals. Indeed, the antidiuretic hormone arginine vasotocin appears to be required to simulate some AQP-mediated water transport in in vitro skin preps (48).…”
Section: Bd Infection Impairs Cutaneous Water Uptake Rates But Not Tosupporting
confidence: 81%
“…We previously showed that epithelial ion transporters in the ventral skin of frogs were similarly upregulated (both at the gene and protein levels) immediately after sloughing, potentially to mitigate high rates of salt loss following sloughing (79). AQP proteins may similarly be highly expressed under conditions requiring large fluxes of water, such as in terrestrial frogs or when animals are dehydrated, where water uptake is essential to maintain proper osmotic balance (64). Such changes in AQP expression during sloughing may be mediated via osmoregulatory hormones (41,83).…”
Section: Aqp and Tight-junction Mrna Response To Sloughing And Bd Infmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we removed possible retro-transposable single exon genes. The resulting gene model contained28,483 protein coding genes…”
mentioning
confidence: 99%